2019
DOI: 10.1109/access.2019.2951999
|View full text |Cite
|
Sign up to set email alerts
|

Resource Allocation Based on Interference Alignment With Clustering for Data Stream Maximization in Dense Small Cell Networks

Abstract: In this paper, by allocating the limited subchannel resources based on interference alignment (IA) with clustering to mitigate the severe co-tier interference in dense small cell networks (SCNs), we aim at maximizing the number of data streams achieved by all small cell user equipments (SUEs) while guaranteeing the data stream requirement for each SUE. As the corresponding optimization problem is NP-hard, we propose a two-phases algorithm based on graph theory to obtain a suboptimal but efficient solution, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Active users in the same sector can be scheduled in an NOMA cluster and served by a randomly directional beam. Each performance curve is obtained by taking the average of 5000 realizations [17], [47]. Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Active users in the same sector can be scheduled in an NOMA cluster and served by a randomly directional beam. Each performance curve is obtained by taking the average of 5000 realizations [17], [47]. Fig.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…The complex multiplication involved in the receiving combining matrices is represented by normalT()21Nu3. The computational complexity of the proposed limited sub‐channel resource allocation based on IA with clustering 90 is observed to be lesser than scriptO()K3+ɸmin()KM+. In a dense SCN to reduce the impact of both co‐tier and cross‐tier interference, Zhang et al 91 proposed an effective subchannel allocation scheme based on IA.…”
Section: Degrees Of Freedom Associated With Various Bia Schemesmentioning
confidence: 99%
“…Although the problem of RA has been thoroughly investigated in the literature [4], [9]- [15], [19], little work focused on RA for mScs. Typically, RA for mScs is performed using mathematical programming, which involves either maximizing the sum rate or minimizing the interference between mScs in the network [6], [8], [20].…”
Section: A Related Workmentioning
confidence: 99%
“…The synergy of NeDe and RA would be highly beneficial, however the RA process has to be optimized specifically for small-cell networks. Therefore, RA for small-cell networks have received significant interest by the research community as reported in [4], [13]- [15], and the references listed therein. Moreover, because cellular users connected from mobile vehicles are among the primary network users, resource allocation for mSc networks has been considered as well [6], [16], [17].…”
Section: Introductionmentioning
confidence: 99%